Effect of SiC Particulate on Glass Fibers Reinforced Polymer Composites in Erosive Wear Environment - R.H. Abdel-Rahim; Z.F. Atya (Engineering and Technology Journal, 2017)
In this study the physical property, mechanical properties and erosion wear of pure epoxy and hybrid composites were studied. Composites were prepared and investigated by Hand lay-up molding. Pure epoxy and hybrid compositions were prepared, 4% and 8% volume fractions of glass fibers as reinforcement and 4% and 8% of SiC as filler particles. The investigated physical property is density while the mechanical property was hardness. Solid particles erosion wear tests are also carried out. The experimental results showed that increased volume fraction of glass fibers to (8%) led to increase the (density). The maximum density is equal (1.661gm/cm3). Hybrid composite with (Epoxy +8%GF+8%SiC) has the maximum hardness of (82) shore D. The particle-contained water jet type experimental erosion test results that the reinforcement volume fraction as well as particles distribution and bonding has considerable effect on the wear of epoxy composites. It was found that the better resistance was for hybrid composites (Epoxy+8%GF+4%SiC) at angle 30°, erodent size 800 μm, and time 10 hour.